The complete mitochondrial genome of Metidiocerus impressifrons (Kirschbaum, 1868) (Hemiptera: Cicadellidae: Idiocerinae) - Mingrui Ma; Zhengnan Li; Xianguang Guo; Bin Zhang (Mitochondrial DNA. Part B. Resources, 2022)
We determined the complete mitochondrial genome (mitogenome) of the leafhopper Metidiocerus impressifrons by next-generation sequencing. The mitogenome sequence was 16,426 bp in length and consists of 13 protein-coding genes, 22 transfer RNA (tRNA) genes, 2 ribosomal RNA (rRNA) genes, and a control region. Moreover, the nucleotide composition biases toward A and T, which together made up 78.2% of the entirety. The complete mitochondrial genomes of Metidiocerus impressifrons and other 27 species were used for phylogenetic analysis using the Bayesian method. The above results would facilitate our understanding of the evolution of Idiocerinae mitochondrial genome.